Functional Identification and Transcriptional Activity Analysis of Dryopteris fragrans HMGR Gene - Meng Sun; Qian Ma; Xueqi Wang; Jialiang Guo; Jiaxuan Wang; Dongrui Zhang; Kirill Tkachenko; Wenzhong Wang; Ying Chang (Plants)
Dryopteris fragrans (L.) Schott synthesizes volatile sesquiterpenes through the mevalonate pathway (MVA), in which 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) serves as the key rate-limiting enzyme. Although HMGR plays a crucial role in terpenoid biosynthesis, its functional characteristics in D. fragrans and its involvement in stress responses remain unclear. This study identified three HMGR genes (DfHMGR1/2/3) from the transcriptome data of D. fragrans. Bioinformatics analysis revealed that the encoded proteins are localized to the endoplasmic reticulum and share high sequence similarity with fern homologs. Under abiotic stress conditions, DfHMGRs exhibited differential expression patterns, with marked upregulation under salt and drought stress. To validate the functions of these genes, we generated transgenic Nicotiana tabacum L. plants overexpressing DfHMGRs. Compared with wild-type controls, the transgenic lines showed enhanced tolerance to drought and heat stress. Promoter analysis identified functional regulatory regions controlling DfHMGR expression, and co-expression network analysis predicted 21 potential transcriptional regulators. This study validates the function of D. fragrans HMGRs in a heterologous system and provides candidate genes for improving stress resistance in plants.